MENGOPTIMALKAN POTENSI DESA KALITAN DALAM RANGKA MELESTARIKAN BUDAYA DAN MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Onery Saputra; Norma Puspitasari; Maulina Isza Fadila; Saputra, Onery Andy (PT Agung Media Publisher, 2024)
The purpose of this community service is to realize the needs of Kalitan Village Kertonatan Sukoharjo in developing proklim kalitan to be known more widely by the community through a clear introduction to the environment using directions. The methods used in this activity are observation, interview and interview. The results obtained from this community service activity are that the authors and the team were able to realize the direction signs for the climate village program in the village of Kalitan Kertonatan Sukoharo including the waste bank, IPAL, Toga, Jambe Spring, Women Farmers Group, and Playground. This is very beneficial for the community because Kalitan village, especially Proklim Kalitan Sukoharjo, becomes more recognized by the community.